Youth baseline and state pain-related injustice appraisals are associated with emotional responses of anger and sadness: An experimental study - Daenen, Frederick; Wauters, Aline; Van Ryckeghem, Dimitri M.L.; Trost, Zina; Vervoort, Tine (Frontiers in Pain Research, 2023)
ABSTRACT Background: Youth pain-related injustice appraisals are associated with adverse functioning; however, mechanisms by which injustice appraisals exert their impact have yet to be elucidated. Adult injustice literature suggests anger, sadness, and attention bias to anger (AB) as potential mechanisms. This study examined the effects of injustice appraisals in a healthy youth sample by applying a justice violation manipulation. We hypothesized the justice violation condition to lead to worse pain outcomes with effects mediated by anger, sadness, and AB as compared to the control condition. We further explored associations between both baseline and state injustice appraisals and anger, sadness, and AB across conditions. Methods: A 2x2 time by condition design was used to test hypotheses. 133 healthy youth aged 9-16 years old completed two cold pressor tasks (CPTs). In the experimental (i.e., justice violation) group, participants were initially told to complete one CPT, but were told afterwards to perform it again due to experimenter negligence. In the control group, no justice violation occurred. Baseline injustice appraisals and pain catastrophizing were assessed with the Injustice Experience Questionnaire and Pain Catastrophizing Scale for Children; state outcomes (i.e., injustice, catastrophizing, anger, sadness) were assessed after CPTs. AB was indexed using a dot-probe task. Results: Findings indicated no effects of the justice violation on pain outcomes or associated mechanisms, nor on injustice appraisals, suggesting manipulation failure. However, across conditions, baseline and state injustice appraisals were positively associated with anger and sadness, but not with AB. Conclusions: Despite the experimental justice violation failing to elicit differential injustice appraisals across conditions, the current study supports both anger and sadness as key emotional responses associated with pain-related injustice appraisals in a healthy youth sample.